Bodies in Expression: Life Experiences, Practices, Aesthetics - Adrián Scribano; Rebeca Cena (Revista Latinoamericana de Estudios sobre Cuerpos, Emociones y Sociedad)
It is with great joy that we share with you the 20th issue of the Latin American Journal of Studies on Bodies, Emotions and Society. This anniversary issue concretises a great shared effort that the Collective Action and Social Conflict Program from CIECS (CONICET-UNC); the Study Group on Sociology of Emotions and Bodies from IIGG-UBA; and the Latin American Network of Social Studies of Emotions and Bodies have been continuously making on a fourmonthly basis since 2009